Diffusion-weighted imaging in the assessment of prostate cancer: Comparison of zoomed imaging and conventional technique. Issue 5 (May 2016) - Brendle, Cornelia; Martirosian, Petros; Schwenzer, Nina F.; Kaufmann, Sascha; Kruck, Stephan; Kramer, Ulrich; Notohamiprodjo, Mike; Nikolaou, Konstantin; Schraml, Christina
Highlights: Image quality in prostate MRI is significantly higher in zoomed DWI. Zoomed DWI improves true positive and false negative rates for prostate cancer. Alignment quality with anatomical images is significantly better using zoomed DWI. Zoomed DWI might improve biopsy and radiation planning due to distortion reduction. Abstract: Purpose: To compare reduced field-of-view (zoomed) diffusion-weighted imaging (DWI) and conventional DWI in the evaluation of prostate cancer with respect to lesion detection, image quality and alignment accuracy. Material and methods: The study was carried out in accordance with the Declaration of Helsinki and was approved by the institutional review board. Image data of 29 histology-proven prostate cancer lesions in 15 patients were evaluated. All patients underwent both conventional DWI and zoomed DWI at 3 T. Zoomed DWI and conventional DWI sequences were analysed qualitatively and quantitatively. Subjective image quality, visual distortion and presence of artefacts were rated on a 5-point Likert scale (1 = excellent) by two readers in consensus. Lesion conspicuity, sensitivity and specificity in lesion detection were evaluated and compared for both DWI sequences using ROC curves and area under the curve (AUC). To analyze the geographic distortion in DWI the alignment accuracy of prostate and lesions was measured in three spatial dimensions referring to the T2-weighted anatomical images as reference. In a region of interest (ROI) evaluation, ADC values were measured in prostate tissue and malignant lesions. Comparison of qualitative and quantitative parameters was performed using Wilcoxon test with subsequent Bonferroni correction. Results: Subjective image quality was rated significantly higher in zoomed DWI compared to conventional DWI (2.1 ± 0.9 vs. 2.7 ± 0.9; p = 0.0375). Visual distortion and artefacts were reduced in zoomed DWI without reaching statistical significance (1.8 ± 0.7 vs. 2.4 ± 1.0 and 2.1 ± 1.0 vs. 2.5 ± 1.0). Sensitivity and specificity of zoomed and conventional DWI were not significantly different. Zoomed DWI had a slightly higher AUC compared to conventional DWI without significant difference (0.82 versus 0.78; p = 0.0576). Lesion conspicuity did not significantly differ between zoomed DWI and conventional DWI (1.8 ± 0.8 vs. 1.9 ± 1.0; p = 0.8523). The alignment accuracy of zoomed DWI was significantly higher regarding both the prostate gland and lesions (deviation of outer contours of lesions in sagittal plane: 3 ± 4 mm vs. 5 ± 3 mm; p = 0.0008). ADC tended to be higher in zoomed DWI without statistical significance (ADCmean in peripheral zone: 1.7 ± 0.2 × 10 −3  mm 2 /s vs. 1.5 ± 0.4 × 10 −3  mm 2 /s; ADCmean in lesion: 1.0 ± 0.71 × 10 −3  mm 2 /s vs. 0.8 ± 0.2 × 10 −3  mm 2 /s). Conclusions: Zoomed technique offers improved image quality for diffusion-weighted imaging of the prostate with reduced image distortion both for the whole gland as well as for cancer lesions and at least comparable diagnostic performance. The zoomed technique could be useful for multiparametric tissue characterization but also for biopsy and radiation therapy planning.